A regenerative Enhanced Geothermal System for heat and electricity production as well as energy storage. (September 2022) - Haris, Muhammad; Hou, Michael Z.; Feng, Wentao; Mehmood, Faisal; Saleem, Ammar bin
Abstract: Enhanced Geothermal Systems (EGSs) evolved from hot dry rock (HDR) can play a crucial role in fulfilling the energy demands while boosting the transition toward carbon neutrality. This study proposed an innovative conception of EGS to integrate heat and electricity production and the storage of surplus renewable energy. Employing engineering data from the GeneSys project, Germany, a geothermal facility is numerically simulated by adopting two horizontal wells. In order to investigate the evolution of fluid and heat transmissivity during fracturing, production, and storage procedures through multiple hydraulic fractures while incorporating stress superposition effects, we performed coupled thermo-hydro-mechanical (THM) modeling with improved simulators, namely FLAC3D plus and TOUGH2MP-TMVOC. By critically optimizing the thermal production, the electric potential caused by reservoir temperature decreases from 7.17 MW to 5.08 MW during 30 years, and the Levelized cost of electricity (LCOE) of proposed EGS is estimated at 5.46 c/kWh; thus indicating remarkable development feasibility from an economic perspective. Finally, we have inspected several schemes for energy storage on the thermal-depleted reservoir to extend the life of geothermal power plant and make surplus energy useable efficiently. The results revealed that the EGS project could indeed be regenerative as formation temperature rises with energy storage/recovery cycles.